Assessing interest in artistic gymnastics - Sands, W. A.; Bogdanis, G. C.; Penitente, G.; Donti, O. (Science of Gymnastics Journal, 2021)
Despite information from world media, worldwide interest in artistic gymnastics has never been assessed. Memberships, equipment and apparel purchases, subscriptions, and other data have been used as indirect substitutes for gauging interest and participation in gymnastics. A readily available tool for assessing gymnastics interest could be of use in uncovering myriad trends. Aim of Study: This study sought to use a relatively new internet search tool called Google TrendsTM (GT) to assess gymnastics interest by records of search terms used in GoogleTM. Methods: GoogleTM searches involve the use of search terms that are recorded and then accessible by GT. As GoogleTM searches provide access to topics of interest nearly anywhere in the world, by anyone with internet access, then using Google TrendsTM, then GT could be used to harvest the number and types of searches involving the search-terms "men`s gymnastics" and "women`s gymnastics." The tally of the search terms was obtained using filters such as country, region, and others. GT reports the search-term trends by calculating a relative percentage based on a sample of the largest number of specific search-term use during a particular time. Although the relative percentage approach is somewhat awkward, processing large amounts of data may be considered valuable and otherwise unattainable. Results and Conclusions: Results should be interpreted cautiously. However, the analysis revealed a litany of important trends in the worldwide interest in gymnastics.